(untitled) (Zaporizhzhia Historical Review, 2021)
This article deals with the processes of development of the metrology in Ukraine. Using documents, the author analyzes the development of technologies through the metrology by today. The main attention in the article is paid to the needs of the Ukrainian industries in men of science in metrology and to the periods of metrology development. The author comes to the conclusion that the scientific potential of metrology development is the most important sphere in the technician Ukraine.